Efeitos do treinamento resistido concêntrico e excêntrico sobre a modulação autonômica cardíaca e parâmetros cardiovasculares - Gois, Mariana de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Introdução: a contração concêntrica promove maior estresse cardiovascular em relação à contração excêntrica, sobretudo por apresentar maiores valores de frequência cardíaca (FC), pressão arterial sistólica (PAS), pressão arterial diastólica (PAD) e pressão arterial média (PAM) em estímulos agudos. Entretanto, no âmbito do treinamento, não se sabe sobre a relação custo benefício destes dois tipos de exercício. Objetivo: avaliar e comparar o efeito de um treinamento resistido, realizado com ênfase concêntrica vs excêntrica, sobre respostas cardiovasculares (PAS, PAD e FC) e autonômicas [variabilidade de frequência cardíaca (VFC)]. Casuística e métodos: o estudo foi composto por 80 homens, com idade entre 18 e 30 anos. Os sujeitos foram alocados em 4 grupos, sendo que os grupos G1 (concêntrico) e G2 (excêntrico) foram submetidos a apenas uma sessão de ER para o grupo extensor do joelho...

Introduction: the concentric contraction causes greater cardiovascular stress in relation to the eccentric contraction, mainly due to the higher values of heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP) and means arterial pressure (MAP) in acute exercise. However, in the training, it is unknown the cost benefit of these two types of exercise. Objective: to evaluate and compare the effect of a resistance training, performed eccentric versus concentric with emphasis on cardiovascular responses (SBP, DBP and HR) and autonomic [heart rate variability (HRV)]. Methods: the study consisted of 80 men, aged between 18 and 30 years. The subjects were divided into 4 groups, with G1 (concentric) and G2 (eccentric) underwent only one session of ER for the knee extensor group [3 sets of 1 rep at 100% of 1 repetition maximum (RM )] and G3 (concentric) and G4 (eccentric) performed 10 sessions of resistance training, in which the 10th session consisted of three sets of 1 rep at 100% of 1RM, also for the knee extensor group. The volunteers were monitored in two conditions: before and 24 hours after the training and before, during and after (45 minutes) the only session of the G1 and G2... (Complete abstract click electronic access below)
Keywords: Fisioterapia; Sistema nervoso autonomo; Muscle strength; Autonomic nervous system